2009
DOI: 10.15298/invertzool.05.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Ampharetidae (Polychaeta) with modified thoracic notopodia

Abstract: Ampharetidae comprises about 300 species and 100 genera, more than 50 are monotipic. As a first step towards a revision of the family, all 30 species with modified thoracic notopodia are reviewed. These 27 species had previously been organized into 11 genera, but several more genera need to be established if we follow a traditional approach to taxonomy of family. Based on a critical re-evaluation of 12 characters commonly used in ampharetid taxonomy and traditional weighting of these characters, it is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 7 publications
2
38
0
Order By: Relevance
“…Anobothrus gracilis is a species described from Swedish coasts and has a wide distribution in the Arctic Ocean, North Atlantic Ocean (Iceland to Swedish West coast), and NW Pacific Ocean (Jirkov, 2008(Jirkov, , 2011Parapar et al, 2014). Anobothrus patersoni is an exclusively abyssal species (3260 -8292 m depth) described from North Pacific (Japan) but recorded also in the North Atlantic (Jirkov, 2008). In the Capbreton Canyon, Rallo et al (1993) found a single specimen of A. gracilis between 358 -410 m, and two incomplete specimens of Anobothrus aff.…”
Section: Description ( Based On Holotype and Paratypes )mentioning
confidence: 99%
“…Anobothrus gracilis is a species described from Swedish coasts and has a wide distribution in the Arctic Ocean, North Atlantic Ocean (Iceland to Swedish West coast), and NW Pacific Ocean (Jirkov, 2008(Jirkov, , 2011Parapar et al, 2014). Anobothrus patersoni is an exclusively abyssal species (3260 -8292 m depth) described from North Pacific (Japan) but recorded also in the North Atlantic (Jirkov, 2008). In the Capbreton Canyon, Rallo et al (1993) found a single specimen of A. gracilis between 358 -410 m, and two incomplete specimens of Anobothrus aff.…”
Section: Description ( Based On Holotype and Paratypes )mentioning
confidence: 99%
“…21 according to Jirkov (2011) or 73 and 71 according to Salazar & Hutchings (2012) and Reuscher et al (2009), respectively). Since papers by Hartley (1985) and Holthe (1986a, b), knowledge of this family has had significant contributions, from Mackie & Pleijel (1995), Jirkov (2001 and Parapar et al (2011Parapar et al ( , 2012 for European waters, and from Hilbig (2000), Holthe (2000), Jirkov (2008), Schüller (2008), Reuscher et al (2009) and Imajima et al (2012Imajima et al ( , 2013 for other oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Reported from worldwide locations but probably restricted to circumpolar areas; specimens from other regions may belong to other species (Jirkov 2008). …”
Section: Checklistsmentioning
confidence: 99%